The Financial Resilience and Life Satisfaction Nexus of Indigenous Australians*. Issue 4 (12th September 2020) - Jayasinghe, Maneka; Selvanathan, Eliyathamby A.; Selvanathan, Saroja
Abstract : Financial resilience is characterised by four sets of variables, namely economic resources, financial inclusion, financial capability and social capital. The purpose of this study is to examine the association between financial resilience and life satisfaction of Indigenous Australians using the (2014/2015) National Aboriginal and Torres Strait Islander Social Survey data. The results reveal that running out of money for living and problems in accessing financial services have significant negative implications on the life satisfaction of Indigenous Australians. The ability to raise money in an emergency, social connections and community support in times of crisis contributes to greater life satisfaction.